Feasibility of computerised positive mental imagery training as a treatment adjunct in in-patient mental health settings: randomised controlled trial - Katharina Westermann; Marcella L. Woud; Jan C. Cwik; Christian Graz; Peter W. Nyhuis; Jürgen Margraf; Simon E. Blackwell (BJPsych Open, 2021)
Background Positive affect and anhedonia are important but challenging targets for mental health treatments. Previous research indicates the potential of a computerised cognitive training paradigm involving generation of positive mental imagery, termed positive mental imagery training (PMIT), to increase positive affect and reduce anhedonia.